VD_FINDINFO Décision / 2014 / 68 vom 17. Januar 2014 - VD Tribunal cantonal (2014)
INDEMNITÉ ÉQUITABLE, INDEMNITÉEN GÉNÉRAL, AVOCAT, ACQUITTEMENT | 393 al. 1 let. a CPP (CH), 429 al. 1 let. a CPP (CH), 429 al. 1 let. b CPP (CH), 429 CPP (CH)